(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
the branch of biology dedicated to the study of animals, offers a captivating journey into the intricate world of living organisms. This scientific article provides an overview of zoology, its significance, key areas of study, and the contributions it makes to our understanding of life on Earth. From taxonomy to ethology, from anatomy to conservation, zoology encompasses a wide range of sub-disciplines that shed light on the diversity, behavior, and evolution of the animal kingdom.